MARKETING TOURISM BASED COMMUNITY BASED TOURISM (CBT) IN ACEH SELATAN - Anismar, Anismar; Akmal, Saiful; Radma, Radma (Jurnal Sosiologi Dialektika Sosial, 2025)
This article discusses community-based tourism marketing (CBT) in South Aceh Regency. The objective of this research is to explore the concept of community-based tourism marketing and its potential for future development. These include marketing to both domestic and international travelers, to attract investors interested in the professional management of tourist attractions. This research discusses the role of the community in creating and developing tourist attractions by promoting them in their own way, without relying on assistance from the government. This research discusses the role of the community in creating/developing tourist attractions by promoting them in their way, without relying on assistance from the government. Data was analyzed using content analysis. This research uses a Community-Based Tourism (CBT) approach. This approach is very appropriate to use for developing community-based tourism programs. The findings in this research show the role of communities in South Aceh in developing tourist attractions in their environment so that they can generate economic income to support the general economy of the community and their businesses in the tourism sector without expecting assistance from the government.